2016
DOI: 10.1016/j.jaci.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Association between domestic water hardness, chlorine, and atopic dermatitis risk in early life: A population-based cross-sectional study

Abstract: Background: Domestic water hardness and chlorine have been suggested as important risk factors for atopic dermatitis (AD). Objective: We sought to examine the link between domestic water calcium carbonate (CaCO 3) and chlorine concentrations, skin barrier dysfunction (increased transepidermal water loss), and AD in infancy. Methods: We recruited 1303 three-month-old infants from the general population and gathered data on domestic water CaCO 3 (in milligrams per liter) and chlorine (Cl 2 ; in milligrams per li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 18 publications
2
60
0
4
Order By: Relevance
“…Inherent properties of the water used for washing may also play an important role. A recent U.K. population‐based study reported that living in a hard‐water area was associated with up to 87% increased risk of AD at 3 months of age; the risk tended to be higher in children with FLG mutations . These findings were recently confirmed in a cohort study from Denmark, where early exposure to hard domestic water was associated with an increase in the relative prevalence of AD in the first 18 months of life .…”
Section: Environmental Factorsmentioning
confidence: 81%
See 1 more Smart Citation
“…Inherent properties of the water used for washing may also play an important role. A recent U.K. population‐based study reported that living in a hard‐water area was associated with up to 87% increased risk of AD at 3 months of age; the risk tended to be higher in children with FLG mutations . These findings were recently confirmed in a cohort study from Denmark, where early exposure to hard domestic water was associated with an increase in the relative prevalence of AD in the first 18 months of life .…”
Section: Environmental Factorsmentioning
confidence: 81%
“…The development of novel prevention strategies focused on the skin barrier is an area of active research. Emerging evidence on the impact of water hardness has raised the question of whether installing domestic water softeners around the time of birth for high‐risk children may prevent the condition from developing in infants. A U.K. interventional trial to test this is in progress (NCT03270566).…”
Section: Preventative Approachesmentioning
confidence: 99%
“…So‐called hard water appears to have the most negative effect on the skin barrier, which, in turn, may increase the risk of AD . Accordingly, a higher prevalence of AD in children residing in regions with hard domestic water has been found . A high calcium carbonate content is normally associated with an elevated pH, which may result in premature activation of serine proteases that, in turn, degrade corneodesmosomes .…”
Section: Discussionmentioning
confidence: 99%
“…The effect estimates remained similar after adjusting for filaggrin genotyping. However, a cross‐sectional analysis of the EAT study identified an increased risk of developing eczema by 3 months of age if the child lived in an area of hard water . Jabbar‐Lopez et al .…”
Section: Innovative Research Findingsmentioning
confidence: 99%